Determinants of External Debt in Thailand and The Philippines - Lau, Evan; Lee, Alvina Syn-Yee (International Journal of Economics and Financial Issues, 2017)
External debt has been the major global concern not only heavily indebted poor countries (HIPCs) but also developing nations in resultants of the 2008 Global Financial Crisis (GFC). It has become a well-discussed subject and generally a concern of global finance and world of economy greatly. This paper analyses the role of some macroeconomic variables in determining the external debt burden in Thailand and the Philippines from 1976 to 2013. The results indicate the existence of short-run linkages originated from inflation rate (CPI) and real interest rate (RIR) to external debt (ED) in the case of Thailand. As for the Philippines, although there is no evidence of short-run linkages origin from GDP, CPI, RIR and M2 to ED, but the burden of short-run adjustment appears to have fallen mostly on GDP and M2. Further, dynamic econometric analysis suggests that money and quasi money (M2) to total reserves ratio is the most exogenous variable beyond the 50-years horizon. The study concludes that a sound debt management could be implemented to control debt accumulation and to reduce dependence on debt relief in the form of foreign aid. Keywords: External Debt Burden; Thailand; the Philippines. JEL Classifications: F34; C22